Resurrection of Rhynchoplax Stimpson, 1858, with the description of two new species from Japan and Australia (Crustacea: Decapoda: Brachyura: Hymenosomatidae) - Komai, Tomoyuki; Poore, Gary C. B. (Zootaxa, 2016)
Rhynchoplax Stimpson, 1858, is resurrected from synonymy with Halicarcinus White, 1846. Rhynchoplax hondai Takeda & Miyake, 1971, a species based on an immature female, is rediagnosed and two new species, R. magnetica n. sp. from northeastern Australia and R. minutula n. sp. from the Ryukyu Islands, Japan, are described. They differ from R. hondai in the shape of the rostrum, form of the subhepatic region and the armature of the pereopodal meri. All differ from the type species R. messor Stimpson, 1858, in having a longer and simple rostrum without supraocular pseudorostral spines and the absence of a postocular spine.